1999
DOI: 10.1046/j.1440-1827.1999.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastoma with basal cell carcinoma‐like feature emerging as a nasal polyp

Abstract: A case of a 63-year-old man with ameloblastoma with basal cell carcinoma (BCC)-like features clinically emerging as a nasal polyp is reported. The left nasal cavity was filled with a solid mass, which seemed to be a sinusitis-associated nasal polyp. The polyp was covered by parakeratotic squamous epithelium which was directly connected to the BCC-like tumor nest. The BCC-like features gradually changed to adamantinoid features. The polyp was connected with a huge mass filling the maxillary sinus and the molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
2
8
1
3
Order By: Relevance
“…The IHC reactions of the known differential biomarkers (EpCam and KL1) of PA and OBCC were found to be identical to previous reports 15. That is, EpCam was exclusively positive in the OBCC and KL1 was exclusively positive in the PA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The IHC reactions of the known differential biomarkers (EpCam and KL1) of PA and OBCC were found to be identical to previous reports 15. That is, EpCam was exclusively positive in the OBCC and KL1 was exclusively positive in the PA.…”
Section: Discussionsupporting
confidence: 85%
“…In conclusion, the present IHC-based, comparative study screened for differentially expressed proteins in the PA and OBCC using 50 antisera, and found that EpCam was exclusively expressed in the OBCC and that KL1 was dominantly expressed in the PA, as previously reported 15. Furthermore, immunostainings of ameloblastin, amelogenin, Krox-25, CEA, E-cadherin, p63, FAK, and cathepsin K were consistently positive in the PA, and N-RAS, TGF-β1, survivin, α1-antitrypsin, TNFα, and MMP-1 were consistently positive in the OBCC.…”
Section: Discussionsupporting
confidence: 80%
“…Examples of ordinary ameloblastoma and PA did not exhibit reactivity for this antibody except of a focus of a PA in which faint cytoplasmic staining was observed. Kato et al 38 have reported negative immunostaining with Ber-EP4 in an ameloblastoma that was characterized by basaloid features. However, one of the authors IGK; (unpublished data) has observed focal positive staining of neoplastic cells in basal cell ameloblastoma.…”
Section: Discussionmentioning
confidence: 98%
“…Ameloblastoma is a common, locally aggressive, odontogenic epithelial neoplasm that develops intraosseously within the tooth‐bearing regions of the maxilla or mandible 3,7,8 . The ameloblast is a secretory cell responsible for the production of dental enamel.…”
Section: Discussionmentioning
confidence: 99%
“…A gingival mass in the premolar region of the mandible in a patient in their fourth or fifth decade is the most common presentation 3,10 . The anticytokeratin antibody KL‐1 and antiepithelial antibody Ber‐EP4 have been reported to be immunohistochemical markers that may be used to distinguish ameloblastoma from BCC 8 . Ber‐EP4 is typically negative in ameloblastoma, whereas KL‐1 is positive.…”
Section: Discussionmentioning
confidence: 99%